The Discourse of a Historian and Administrator in Yevgeny Feoktistov’s Notes from What Has Been Heard and Seen (ENTHYMEMA, 2017)
There is no unambiguous perspective on Russia’a cultural and political processes of the second half of the 19th century. Their patterns are largely approached through the lens of the key figures that had a determining influence at a relevant period. Yevgeny Feoktistov was a writer, a journalist, a staff member of the magazines Sovremennik and Otechestvennye Zapiski, the editor of Russkaya Rech and Journal of the Ministry of National Enlightenment (1871–1883), later a censor, the privy councillor (since January 1, 1883), the head of the Central Administration for Printing Press for almost 13 years (1883–1896) (Russia’s censor-in-chief), a senator (from May 23, 1896 until his death), and part of Russia’s administrative elite. He came an impressive way of personal growth that brought him from the ranks of active liberals and Otechestvennye Zapiski journalists to the position of Russia’s censor-in-chief, who signed the order to close that same magazine twenty years later. His biography is partly captured in Ivan Goncharov’s novel The Same Old Story. This article investigates the modifications of linguistic peculiarities in Feoktistov’s essays and statements and draws his linguistic portrait, which doesn’t only explain the patterns of his behavior and everyday style but also sheds light on the shady sides of the events that Russia witnessed in the 1860s–1890s and shapes new optics of the elite circles Feoktistov was part of.